2020
DOI: 10.3389/fmech.2020.576642
|View full text |Cite
|
Sign up to set email alerts
|

Electric Vehicle Battery Disassembly Sequence Planning Based on Frame-Subgroup Structure Combined with Genetic Algorithm

Abstract: Since the electric vehicle battery (EVB) is wildly recycled in industry, the disassembly procedures of variable EVBs is so important that can influence the efficiency and environmental impacts in remanufacturing. To improve disassembly efficiency in EVB remanufacturing, a disassembly sequence planning method based on frame-subgroup structure is proposed in this paper. Firstly, the improved disassembly relation hybrid graph and disassembly relation matrix are proposed to identify the disassembly precedence rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This question leads to an optimization problem that must be solved for individual batteries to significantly increase the economic efficiency of disassembly as the most expensive processing step in the current state [11]. Ke et al [12] performed disassembly tests on the same battery type with the same skilled workers. They observed that the workers could disassemble the battery at least 11.5% faster when they had an optimized disassembly sequence.…”
Section: Extraxtormentioning
confidence: 99%
See 4 more Smart Citations
“…This question leads to an optimization problem that must be solved for individual batteries to significantly increase the economic efficiency of disassembly as the most expensive processing step in the current state [11]. Ke et al [12] performed disassembly tests on the same battery type with the same skilled workers. They observed that the workers could disassemble the battery at least 11.5% faster when they had an optimized disassembly sequence.…”
Section: Extraxtormentioning
confidence: 99%
“…In this way, different decisions can be made with the help of the optimizer, such as the optimal number of tool and direction changes as well as optimal circular economy strategies at the component level. In the context of battery disassembly, Ke et al [12] proposed a disassembly sequence planning approach for EVBs based on a genetic algorithm using a frame-subgroup structure. The presented method has better convergence properties compared to other genetic algorithm implementations.…”
Section: Adaptive Plannermentioning
confidence: 99%
See 3 more Smart Citations